2019
DOI: 10.1364/oe.27.022074
|View full text |Cite
|
Sign up to set email alerts
|

Distributed fiber optics 3D shape sensing by means of high scattering NP-doped fibers simultaneous spatial multiplexing

Abstract: A novel approach for fiber optics 3D shape sensing, applicable to mini-invasive bio-medical devices, is presented. The approach exploits the optical backscatter reflectometry (OBR) and an innovative setup that permits the simultaneous spatial multiplexing of an optical fibers parallel. The result is achieved by means of a custom-made enhanced backscattering fiber whose core is doped with MgO-based nanoparticles (NP). This special NP-doped fiber presents a backscattering-level more than 40 dB higher with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Similarly, strain sensing requires 3-4 fibers (typically, three fibers for shape sensing, four fibers when temperature compensation is also accounted [22]) for each device under test. The epidural needle investigated in [21] requires interrogation over an 8 cm length, which is easily achieved by each fiber configuration. The analysis shows the feasibility, up to over 1 meter using M01 fibers, of using the MgO-NP fiber, not only for sensing, but also for covering the whole distance from the interrogator, leading out of the splitter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, strain sensing requires 3-4 fibers (typically, three fibers for shape sensing, four fibers when temperature compensation is also accounted [22]) for each device under test. The epidural needle investigated in [21] requires interrogation over an 8 cm length, which is easily achieved by each fiber configuration. The analysis shows the feasibility, up to over 1 meter using M01 fibers, of using the MgO-NP fiber, not only for sensing, but also for covering the whole distance from the interrogator, leading out of the splitter.…”
Section: Discussionmentioning
confidence: 99%
“…The solution proposed by the authors, instead, makes use of a fiber doped with nanoparticles based on MgO (MgO-NP) within the core as the sensing fiber, which guarantees a scattering gain up to 49 dB. A detail of the fabrication of the fiber was previously reported by Blanc et al [20,25] and subsequently by Beisenova et al [18,19,21], while Section 4 of this work describes the specific scattering performance of the fiber in the context of SLMux.…”
Section: High Scattering Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…A setup for multiplexed distributed optical fiber sensors, which are capable to measure temperature in the range of up to 140 • C (of interest for biomedical applications such as thermo-therapy) with a spatial resolution of 2.5 mm over the several fibers simultaneously, has been reported in [197]. Finally, this approach is also applicable for strain measurements and 3D shape sensing [198,199].…”
Section: Phase-separated Fibersmentioning
confidence: 99%
“…The application was 3D shape sensing with optical backscatter reflectometry in a spatial multiplexing way. 5 Apart from MgO doping, research has reported that high temperature distributed sensing has a better stability with optical fibre doped with gold-zirconia NPs than SMF-28. 6 These new developments encourage researchers to perform further research about NPs in optical fibres and its applications.…”
Section: Introductionmentioning
confidence: 99%